2018
DOI: 10.1098/rsos.171280
|View full text |Cite
|
Sign up to set email alerts
|

Field energetics and lung function in wild bottlenose dolphins,Tursiops truncatus, in Sarasota Bay Florida

Abstract: We measured respiratory flow rates, and expired O2 in 32 (2–34 years, body mass [Mb] range: 73–291 kg) common bottlenose dolphins (Tursiops truncatus) during voluntary breaths on land or in water (between 2014 and 2017). The data were used to measure the resting O2 consumption rate (V˙O2, range: 0.76–9.45 ml O2 min−1 kg−1) and tidal volume (VT, range: 2.2–10.4 l) during rest. For adult dolphins, the resting VT, but not V˙O2, correlated with body mass (Mb, range: 141–291 kg) with an allometric mass-exponent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 63 publications
(124 reference statements)
5
46
0
Order By: Relevance
“…If the dolphins had been stressed or uncomfortable with the procedure, we would have expected to see systematic changes with time. In addition, the f R was within the range previously reported for bottlenose dolphins (Fahlman et al, , 2018a, suggesting that the data reported prior to a breath-hold (Table 1) were normal. During a surface breath-hold, gas is exchanged between the lungs and the blood; O 2 is taken up and CO 2 diffuses from the blood into the lungs.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…If the dolphins had been stressed or uncomfortable with the procedure, we would have expected to see systematic changes with time. In addition, the f R was within the range previously reported for bottlenose dolphins (Fahlman et al, , 2018a, suggesting that the data reported prior to a breath-hold (Table 1) were normal. During a surface breath-hold, gas is exchanged between the lungs and the blood; O 2 is taken up and CO 2 diffuses from the blood into the lungs.…”
Section: Discussionsupporting
confidence: 82%
“…While some researchers rightly consider results obtained from animals under human care not to be perfectly representative of their free-ranging counterparts, certain information is virtually impossible to obtain from wild populations where controlled studies are extremely challenging to carry out. For that reason, we previously compared lung function values and metabolic rates in bottlenose dolphins under managed care, with both nearshore and pelagic populations, and have shown that results obtained with trained cetaceans do provide useful physiological information (Fahlman et al, , 2018a. Thus, the data from the current study provide baseline lung function estimates from healthy dolphins under a situation with minimal stress.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The advancement of common bottlenose dolphin health assessments, transitioning from initial population assessments to endangered species conservation applications has occurred over several decades, expanding knowledge of marine mammal medicine and science. As veterinary standards for dolphins in human care have evolved, so have the standard protocols for handling and monitoring free-ranging dolphins, and diagnostics such as clinicopathology, ultrasonography, radiography, electrocardiography, respirometry, microbiology, and morphometry (29,32,43,77,104,108,180,181). Dolphin health assessments are a valuable tool to extrapolate from the individual to understanding both population and ecosystem health.…”
Section: Resultsmentioning
confidence: 99%
“…From examining dolphin communication to understanding energetics, lung capacity, respiratory metabolomics, and the mechanisms involved in deep diving physiology, health assessments are contributing to advancing scientific knowledge (108,(177)(178)(179). Scientists have improved our understanding of dolphin anatomy and physiology by observing natural behavior during health assessments and monitoring activity and behavior post handling.…”
Section: International Perspectivementioning
confidence: 99%